THE METHOD OF INVARIANT-SPATIAL CODING OF BINARY SEQUENCES - Юдін, О. К.; Курінь, К. О.; Зюбіна, Р. В. (Science-based technologies, 2014)
The expedience of the appliyng of the coding methods which are different from statistical methods in the tasks of data compression is grounded. The offered method of data coding, invariant to statistical, is a method invariant-spatial code (ISK). The cross-correlation sign of binary sequences is defined: summary bit correlation of binary sequence. The definition of the procedure of codingaccording to the certain cross-correlation sign is formulated. In obedience to it the ISK code is an appropriation of sequence number of the binary sequence in a cross-correlation group to it. The rule of calculation of sequence number of ISK of binary sequence in a cross-correlation group by value of the total bit correlation of binary sequence is first described and proved. The method of efficiency estimation of the provided compression procedure which is provided with the offered coding method is first described. The estimation of the expected minimum compression coefficient for the sequences of different length is provided and comparison by this parameter with the methods of the classes of unstatistical compression is made. The assessment of compression coefficient for binary sequence in content of discrete cosine transformant is provided and comparison by this parameter with related coding method is provided. The received results allow making a conclusion about expediency of use of the offered method of coding in technologies of images compression.